(untitled) (REMUNOM, 2026)
This study aimed to correlate water quality parameters and land use classes in the sub-basins of the São Tomás River Basin, located in the municipalities of Rio Verde and Santa Helena de Goiás – GO, Brazil (coordinates 17°43’ to 18°06’S and 50°25’ to 51°10’W). Water samples were collected at the end of the dry season and the beginning of the rainy season (2024/2025) at 15 georeferenced points in the sub-basins of: Cachoeira Stream, Ribeirão das Abóboras, Rio do Peixe, Ribeirão Douradinho, and Ribeirão Campo Alegre. The parameters evaluated included Alkalinity, Nitrate, Nitrite, Turbidity, Temperature, Electrical Conductivity, Oxidation-Reduction Potential (ORP), and Hydrogen Potential (pH). MAPBIOMAS images from 2022 (Sentinel 2, 10m resolution) were used to identify land use and land cover classes in the watershed. Using the land use data, area quantities were extracted, and the percentages of land use classes for each sub-basin were obtained and correlated with the evaluated water parameters. Over 80% of the basin is occupied by land use classes (Pasture, Mosaic of Uses, and Temporary Crops), while less than 10% corresponds to natural cover (Forest Formation and Savanna Formation). A strong negative correlation was found between the Silviculture class and water temperature (r: -0.721), the Temporary Crops class and the Turbidity parameter (r: -0.707), and also the Temporary Crops class and Turbidity (r: -0.707). A strong positive correlation was found between the Urbanized Area class and the parameters Hydrogen Potential (r: 0.976) and Electrical Conductivity (r: 0.884). The results allow for the evaluation of the relationship between land use and water quality, as well as the land uses with the greatest weight and influence on altering water quality parameters